(untitled) (Research, Society and Development, 2021)
Intracanals medications with antimicrobial activity are important as adjuvants in disinfecting the root canal system. Therefore, this study evaluated, in vitro, the pH and antimicrobial activity of a new bioceramic intracanal medication (Bio-C Temp) compared to calcium hydroxide (HC) medications. The determination of pH was carried out by means of a pH meter in the periods of 30 minutes, 3, 24, 72 and 168 hours. The medications Ultracal®XS, Calcium hydroxide with saline (HC/Saline), Calcium hydroxide with propyleneglycol (HC/PG) and Bio-C Temp (bioceramic) were tested against biofilms of two strains of Enterococcus faecalis (ATCCs 29212 and 4083) using direct contact (DCT) and membrane restricted (MRT) tests. Bacterial survival was determined by counting colony-forming units (UFCs) and the data were compared statistically (P < 0.05). The Bio-C Temp paste showed the lowest pH value in the evaluated times. The HC/Saline and HC/PG groups showed greater action compared to the control in the DCT (P < 0.05) against the two strains tested. In addition, HC/PG showed greater antibacterial activity than Bio-C Temp (P < 0.05). All groups showed a difference compared to the control group in the MRT against strain 29212, and only HC/PG showed a significant difference compared to the control against biofilms of strain 4083. Bio-C Temp showed antibacterial action similar to Ultracal®XS, however showed less action in relation to HC/PG. The calcium hydroxide paste associated with propylene glycol showed advantages over the others tested.